Strategies in alpine snowboard parallel giant slalom - a GNSS field study with the Swiss national team - van Wijnkoop, D.; Gander, M.; Bruhin, B.; Kredel, R. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Many factors influence performance in alpine snowboarding. Until now, only very few have been scientifically researched. The aim of this study was to investigate the influence of known factors on performance from alpine skiing in alpine snowboarding. For example, the curve phase distribution and the turn radius were examined.